Ambition, anxiety and aspiration: the use and abuse of Cambridge University's ten‐year divinity statute. Issue 248 (21st November 2016) - Slinn, Sara
Abstract: This article examines the uses to which Cambridge University's ten‐year statute was put suggesting that its popularity from c .1815 reflects both increasing career insecurity among non‐graduate clergy, and the closing of traditional non‐graduate routes into the Anglican ministry. Using a quantitative study of university calendars and ordination records alongside a review of controversial pamphlet literature, the article documents the degree's changing popularity and the appearance of a discourse which discredited both it and non‐graduate clergy. This discourse also reflects the general anxieties of elite and middling families, threatened by meritocratic trends and eager to secure cultural, occupational and economic privilege.